1996
DOI: 10.1161/01.res.79.5.1039
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilatory Effect of Pulsatile Pressure on Coronary Resistance Vessels

Abstract: Intramyocardial pressure becomes high in systole and decreases in diastole. Therefore, the transmural pressure of the intramyocardial vessels is pulsatile, resulting in the cyclic distension of these vessels. However, the effect of pulsatility on the behavior of the coronary resistance vessels has not been evaluated. To assess the influence of pulsatile pressure on the behavior of the coronary arterioles, we measured the luminal cross-sectional area (CSA) of coronary arterioles under cyclically changing transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 16 publications
2
35
0
1
Order By: Relevance
“…In our studies, incubating the segments at 50 mm Hg, the application of a preliminary conditioning pressure cycle of up to 150 mm Hg, applying a continuous pressure change at a rate of about 0.5 mm Hg/s instead of sudden step-like increases, mostly prevented the appearance of the stretch response during recorded cycles. The validity of our approach to measure the elastic properties in spontaneous contraction after the application of mechanical conditioning is supported by recent observations of Goto et al [41]. They found that pulsatile pressure cycles supposed to mimic in vivo changes in transmural pressure load in intramyocardial arterioles have a relaxing (i.e.…”
Section: Discussionsupporting
confidence: 67%
“…In our studies, incubating the segments at 50 mm Hg, the application of a preliminary conditioning pressure cycle of up to 150 mm Hg, applying a continuous pressure change at a rate of about 0.5 mm Hg/s instead of sudden step-like increases, mostly prevented the appearance of the stretch response during recorded cycles. The validity of our approach to measure the elastic properties in spontaneous contraction after the application of mechanical conditioning is supported by recent observations of Goto et al [41]. They found that pulsatile pressure cycles supposed to mimic in vivo changes in transmural pressure load in intramyocardial arterioles have a relaxing (i.e.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, pulsatile change in transmural pressure may be involved in the autoregulation of flow, especially in some tissues such as myocardium. 14 On the other hand, chronically altered mechanical forces usually induce adaptive alterations of vessel wall shape and composition, which is termed vascular remodeling. [15][16][17] It has been shown that acute and transient high intraluminal pressure cause endothelial dysfunction and impaired endothelium-dependent vascular dilation.…”
Section: Discussionmentioning
confidence: 99%
“…Larger pulse pressures (over 40 mm Hg) result in the dilatation of large and small arteries via an endothelium-independent mechanism [130], observations which can be attributed to the well-known plastic properties of the vascular wall, i.e. above a critical distension the cross-links formed between contractile filaments are disrupted and the vessel diameter increases passively [131].…”
Section: Response To Shear Stress and Pulsatile Stretch In Intact Vasmentioning
confidence: 99%